Coulomb interaction-induced jitter amplification in RF-compressed high-brightness electron source ultrafast electron diffraction. (3rd February 2017) - Qi, Yingpeng; Pei, Minjie; Qi, Dalong; Li, Jing; Yang, Yan; Jia, Tianqing; Zhang, Shian; Sun, Zhenrong
Abstract: We have theoretically and experimentally demonstrated an RF compression-based jitter-amplification effect in high-brightness electron source ultrafast electron diffraction (UED), which degrades the temporal resolution significantly. A detailed analysis and simulations reveal the crucial role of the longitudinal and transverse Coulomb interaction for this jitter-amplification effect, which accord very well with experimental results. An optimized compact UED structure for full compression has been proposed, which can suppress the jitter by half and improve the temporal resolution to sub-100 fs. This Coulomb interaction-induced jitter amplification exists in nearly the whole ultrafast physics field where laser-electron synchronization is required. Moreover, it cannot be suppressed completely. The quantified explanation for the mechanism and optimization provides important guidance for photocathode accelerators and other compression-based ultrashort electron pulse generation and precise control.